Book Review: Exile in Colonial Asia: kings, convicts, commemoration (ed. Ronit Ricci) - Ahmad, Siti Nuraishah (Department of English Language and Literature, KIRKHS International Islamic University Malaysia, 2017)
The essays in Exile in Colonial Asia: Kings, Convicts, Commemoration, edited by Ronit Ricci, are the result of a workshop held at the Australian National University in 2013. They examine the many experiences, practices and outcomes of exile in colonial Asia, spanning a period between the 16th century and the early 20th century, over a vast geographical space. The outstanding feature of this volume is the multiple approaches to the subject of exile – literary, anthropological and historical; textual analysis, archival research and fieldwork – which makes it an engaging read.